Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 398709 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Fringilla coelebs Linnaeus, 1758", { "or" : [ "Country is Norway", "Country is Sweden", "Country is Finland", "Country is Denmark" ] }, { "or" : [ "Month is April", "Month is May", "Month is June", "Month is July" ] } ] } The dataset includes 398709 records from 39 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000854-150721130643939/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences